Relationship between depression, anxiety, stress and smartphone addiction in COVID-19 nursing students - Marilyse de Oliveira Meneses; Elaine Maria Leite Rangel Andrade (Universidade de São Paulo, 2024)
Objective: to verify the relationship between symptoms of depression, anxiety, stress and smartphone addiction in COVID-19 nursing students. Method: this was a descriptive-analytical study of 206 nursing students. A sociodemographic characterization and smartphone use instrument adapted from the literature and the following scales Depression, Anxiety and Stress Scale and Smartphone Addiction Inventory were used for data collection. Sociodemographic data and smartphone use were analyzed using descriptive statistics and the relationship between symptoms of depression, anxiety, stress and smartphone addiction was analyzed using multiple logistic regression. Results: the prevalence of smartphone addiction among nursing students was 129 (62.6%) and there was a relationship between symptoms of moderate depression (p=0.049), severe/very severe depression (p=0.005) and mild anxiety (p=0.028) and severe/very severe anxiety (p=0.019) and smartphone addiction. Conclusion: the data show that the construction and implementation of smartphone use policies in the academic and hospital context to prevent smartphone addiction and control associated risk factors is necessary.